CORRELATION BETWEEN SEAGRASS DENSITY WITH GASTROPOD DENSITY IN THE WATERS OF PONCAN GADANG ISLAND SIBOLGACITY OFNORTH SUMATERA PROVINCE - Yulinda, Emelda; Efriyeldi, Efriyeldi; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract                This research was conducted inSeptember 2017 inthe waters of Poncan Gadang Island, Sibolga City, North Sumatera Province. The purpose of this research was to analyze seagrass density, gastropod density and correlation between seagrass density with gastropod density.The method used was survey method. Water qualities  measured were salinity, temperature, transparancy, water pH and current velocity. A research was found 4 species of seagrass with highest density was found at station II(103 ind/m2) and lowest density was found at station III  (69.44 ind/m2).Gastropod consist of 9 species with highest density was found at station II(32.11ind/m2) and lowest density was found at station III(21.33ind/m2). The average value of diversity index was 1.65, the average value of uniformity index was 0.36 and the average value of dominance index was 0.44. That showed the diversity index was moderate, uniformity index was low and none of species that has dominance. Correlation between seagrass density with gastropod density showed strength relationship positive with r value was 0.709. Key Words : Gastropod, Seaggrass, Correlation, Poncan Gadang Island